(untitled) (Journal of the College of Basic Education, 2026)
The role of women is considered one of the most important social roles in building and developing society. The social role of women is defined as a set of actions, activities, and efforts exerted by women in various social and economic fields within the social structure. The current research aimed to: Identify the social role of women among female faculty members and employees at the College of Basic Education, Al-Mustansiriya University, in general. Examine the significance of differences in the social role of women between faculty members and administrative employees. To achieve the objectives of the research, the researcher developed a scale titled "The Social Role of Women in Building the Family and Society", consisting of 40 items distributed over two domains: Family and Society. Based on Social Role Theory, the researcher extracted several psychometric indicators including item discrimination, the correlation of each item with the total scale score, the correlation with its respective domain score, as well as measures of face validity, construct validity, and reliability. All statistical procedures demonstrated that the scale effectively measures the intended variables and domains.The final results revealed that women play a clear and effective role in building both the family and society. Furthermore, the results showed statistically significant differences in favor of the female faculty members. Based on these findings, the researcher presented a set of conclusions, recommendations, and proposals for future studies.